Die Aufnahme des Screenings auf Gestationsdiabetes mellitus in die Mutterschaftsrichtlinien aus Sicht niedergelassener Gynäkologen: Eine qualitative Studie - Diehl, Katharina; Bock, C.; Maul, H.; Kleinwechter, H.; Schneider, S.; Goerig, Tatiana (Zeitschrift für Geburtshilfe und Neonatologie, 2015)
Background: In March 2012, the screening for gestational diabetes was included as a 2-step screening into the German maternity directive. However, up to now it is unclear what resident gynaecologists, who are affected directly by this change in the maternity directive, think about the inclusion of the screening and the kind of screening introduced. Methods: In order to approach this topic from a scientific point of view, gynaecologists in the German cities Mannheim, Ludwigshafen, and Heidelberg were interviewed face-to-face using a semi-structured interview guide with open-ended questions (mean interview length: 33:12 min). The interviews were audiotaped, transcribed verbatim (191 pages), coded by 2 independent reviewers, and analysed using qualitative content analysis. Results: The majority of the gynaecologists supported the introduction of the screening into the maternity directives. However, some gynaecologists felt that this amendment is not strong enough criticising the GCT with 50 g glucose. Many gynaecologists would prefer an oral glucose tolerance test (OGTT, 75 g glucose). But there were also some gynaecologists who thought that the OGTT would strain pregnant women too much and thus deemed it unsuitable for a screening. Additionally, the gynaecologists named difficulties concerning the implementation of the test such as, for example, the non-availability of a ready-made glucose syrup for the GCT and the delayed introduction of billing codes. Discussion: In the framework of this qualitative study, resident gynaecologists - the main actors in the conduct of the screening - had the possibility to offer their opinion on this current topic. The results provide a first insight into the conduct of the screening and may serve as a basis for larger, quantitative studies.
CRIS-Team Scopus Importer:2021-12-06
Keywords: evidence-based antenatal care; gestational diabetes; maternity care directive; pregnancy; prevention